Desain Papan Permainan Tokoh Ibnu Battuta - Alfani, Muhammad Hasanudin; Albar, Deni (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2023)
Ibn Battuta was a Muslim born in the Moroccan population of the Muslim cities of Ibn Battuta, the city of Tangier. Born and raised in the town of Tangier, Ibn Battuta dreamed of traveling to cities far from where he lived. Until he decided to follow the trail of the dream on an expedition. The exploratory story has been written in the book entitled "rihla" but few know of it's existence, and the absence of any visual element found in it. This causes a lack of public interest in reading the story of Ibn Battuta from the book of rihlah. Not a few people are interested in learning the story of Ibn Battuta, but the problem of the lack of information telling the book's existence and the lack of visual elements that are at present a cause for the lack of interest. It could also be an opportunity to inform the public about the story of Ibn Battuta with more interesting delivery. The boardgames is a preferred solution to inform the public of the Ibn Battuta character, because games are one of the popular activities, as well as these games the public can imagine the Ibn Battuta on an exploration route.